2014
DOI: 10.1002/hup.2400
|View full text |Cite
|
Sign up to set email alerts
|

Plasma dehydroepiandrosterone sulfate levels in patients with major depressive disorder correlate with remission during treatment with antidepressants

Abstract: These findings suggest that plasma DHEA-S levels can be used as a putative indicator of the state of remission in patients with major depressive disorder. Copyright © 2014 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…However, it may seem inconsistent with cross-sectional studies showing DHEA(S)-differences in remitted compared to depressed MDD-subjects and associations between DHEAS and MDD-symptom severity (Michael et al, 2000). Moreover, previous studies showed associations between DHEA(S)-reductions and remission during antidepressant treatment (Fabian et al, 2001;Hsiao, 2006;Morita et al, 2014;Paslakis et al, 2010;Schule et al, 2009). However, other studies suggested that these associations between DHEA(S) and remission already exist before treatment (Goodyer et al, 2003;Kurita et al, 2013;Markopoulou et al, 2009) or even before MDD-onset (Goodyer et al, 2000).…”
Section: Trait Vs Statementioning
confidence: 89%
See 1 more Smart Citation
“…However, it may seem inconsistent with cross-sectional studies showing DHEA(S)-differences in remitted compared to depressed MDD-subjects and associations between DHEAS and MDD-symptom severity (Michael et al, 2000). Moreover, previous studies showed associations between DHEA(S)-reductions and remission during antidepressant treatment (Fabian et al, 2001;Hsiao, 2006;Morita et al, 2014;Paslakis et al, 2010;Schule et al, 2009). However, other studies suggested that these associations between DHEA(S) and remission already exist before treatment (Goodyer et al, 2003;Kurita et al, 2013;Markopoulou et al, 2009) or even before MDD-onset (Goodyer et al, 2000).…”
Section: Trait Vs Statementioning
confidence: 89%
“…trait instead of state) [present data and (Girdler et al, 2012)]. On the other hand, DHEA(S) is cross-sectionally associated with MDD-symptom severity (Michael et al, 2000) and successful treatment with antidepressants (Morita et al, 2014;Paslakis et al, 2010;Schule et al, 2009). This seems to be similar to what have been demonstrated for cortisol ; several explanations for these apparent inconsistencies could be thought of.…”
Section: Trait Vs Statementioning
confidence: 92%
“…Some authors found lower DHEA-S levels in MDD patients than in healthy subjects [22,23], while others reported increased ones in MDD patients with [24,25] or without psychotic symptoms [26]. In addition, some authors reported that DHEA-S is negatively correlated with the severity of depressive symptoms [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some authors reported that DHEA-S is negatively correlated with the severity of depressive symptoms [23]. In contrast, in a further paper, the hormone concentrations were found to be reduced in patients who adequately responded to antidepressant treatment, while they remained altered in nonremitters [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite such findings with exogenously administered DHEA(S), the role of endogenous DHEA(S) in neuropsychiatric illness in humans and in MDD in particular, remain unclear. Previous findings in depression have found DHEA and/or DHEA-S concentrations to be decreased (Michael et al, 2000; Mocking et al, 2015; Morgan et al, 2010; Zhu et al, 2015), increased (Assies et al, 2004; Kurita et al, 2013; Morita et al, 2014; Takebayashi et al, 1998), or unchanged (Fabian et al, 2001; Kurita et al, 2013; Markopoulou et al, 2009; Mocking et al, 2015; Paslakis et al, 2010; Romeo et al, 1998) (also reviewed in Maninger et al ., 2009) in depression, compared to non-depressed controls. The relationship between endogenous serum DHEA(S) levels and likelihood of antidepressant-associated remission also remain unclear.…”
Section: Introductionmentioning
confidence: 87%